In situ microscopy for plasma erosion of complex surfaces - Ottaviano, Angelica; Thuppul, Anirudh; Hayes, John; Dodson, Chris; Li, Gary Z.; Chen, Zhitong; Wirz, Richard E. (Review of scientific instruments, 2021)
A novel method for the in situ visualization and profilometry of a plasma-facing surface is demonstrated using a long-distance microscope. The technique provides valuable in situ monitoring of the microscopic temporal and morphological evolution of a material surface subject to plasma–surface interactions, such as ion-induced sputter erosion. Focus variation of image stacks enables height surface profilometry, which allows a depth of field beyond the limits associated with high magnification. As a demonstration of this capability, the erosion of a volumetrically featured aluminum foam is quantified during ion-bombardment in a low-temperature argon plasma where the electron temperature is ∼7 eV and the plasma is biased relative to the target surface such that ions impinge at ∼300 eV. Three-dimensional height maps are reconstructed from the images captured with a long-distance microscope with an x–y resolution of 3 × 3 μm2 and a focus-variation resolution based on the motor step-size of 20 μm. The time-resolved height maps show a total surface recession of 730 μm and significant ligament thinning over the course of 330 min of plasma exposure. This technique can be used for developing plasma-facing components for a wide range of plasma devices for applications such as propulsion, manufacturing, hypersonics, and fusion.